Exploring the effects of extensive reading strategies on grade 10 EFAL learners' academic performance : a case of Kgolakaleleme Secondary School - Mokwalakwala, Motsatsi Jeanet (My University, 2022)
There is a high failure rate experienced in public schools, mostly those that are based in rural areas. This is because learners in rural areas are disadvantaged in terms of exposure to English First Additional Language (EFAL) as the Language of Teaching and Learning (LoTL). They need basic attention in reading as well as writing skills. This was the reason; this study explores the effects of extensive reading strategies on grade 10 EFAL learners’ academic performance. Reading and writing is not an educational problem affecting only learners at FET Phase in schools. The purpose of this study was to see if reading skills grade 10 learners of Kgolakaleleme Secondary School gained from reading club was anticipated to help improve learners’ performance. The method used in this study was qualitative and it is used for teachers to bring out their experiences on EFAL teaching. Data collection was done through structured interviews and non-participant observation. Four teachers of which one is also the Head of Department (HOD) of Languages Department, were sampled from Kgolakaleleme Secondary School in Rakwadu 2 Circuit. The research results from interviews, focus group discussion, observations and document analysis are conjointly presented to avoid recurrences. In this study, qualitative research was employed to examine the impact of extensive reading as it is explored in reading club of the sampled school of Rakwadu 2 circuit on grade 10 learners’ performance. A phenomenological case study was used as the knowledge is contextual in nature. This study falls within the constructive paradigm because knowledge is studied and altered. It was found that leaners distance themselves from reading aloud in the presence of their peers because they have fear of being laughed at and as a result they do not improve their reading skills. This study has revealed that teachers tend to omit some stages of the reading process, say the pre-reading, because they rush to complete the syllabus. Additionally, learners were not granted options to choose from digital material or printed study material due to the inadequate technological infrastructure of the school and the fact that they are located in rural area characterized by poverty and unemployment. Amongst the findings revealed by the study, there are those teachers who did not take English as their major subject in their teaching career. This is one of the contributing factors reading at FET Phase in rural schools is practically unachievable.
Thesis (M.A (Language Education)) -- University of Limpopo, 2022
Keywords: English language; Reading Skills; Writing skills; Academic performance; Tenth grade (Education); English language -- Grammar -- Study and teaching; Reading Skills Competency Tests; Academic achievement; English language -- Study and teaching; Education, Secondary -- South Africa -- Limpopo